2016
DOI: 10.5664/jcsm.6046
|View full text |Cite
|
Sign up to set email alerts
|

Pain Intensity and Opioid Utilization in Response to CPAP Therapy in Veterans with Obstructive Sleep Apnea on Chronic Opioid Treatment

Abstract: Study Objectives: Sleep fragmentation has been linked to poor pain tolerance and lowered pain threshold. Little evidence exists on whether continuous positive airway pressure (CPAP) adherence in veterans with obstructive sleep apnea (OSA) who are taking opioids for non-malignant pain would ameliorate pain and reduce consumption of opioids. Methods: A retrospective case-control study was performed at a VA sleep center. Pain intensity was assessed using the Numerical Categorical Scale prior to CPAP treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In keeping with population norms [32], the back was the most frequently reported location of chronic pain (48.57%). The high frequency of chronic pain in this sample is of clinical importance for treating sleep disorders as pain intensity has been shown to predict PAP nonadherence [16]. In the present study, the majority of patients diagnosed with OSA had chronic pain (81.82%).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In keeping with population norms [32], the back was the most frequently reported location of chronic pain (48.57%). The high frequency of chronic pain in this sample is of clinical importance for treating sleep disorders as pain intensity has been shown to predict PAP nonadherence [16]. In the present study, the majority of patients diagnosed with OSA had chronic pain (81.82%).…”
Section: Discussionmentioning
confidence: 49%
“…The majority of participants reported chronic pain, and this investigation found that measures of sleep fragmentation and hypoxemia were not related to pain intensity among individuals referred to a sleep center. This study highlights the importance of identifying individuals with comorbid OSA/insomnia as effective treatment of their sleep problems may be complicated by the existence of comorbid sleep disorders [30,31] and chronic pain [16], which is likely to be present in this population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This study is also limited due to the nature of using a historical control. [ 14 ] Although the control used mimicked the experimental group in most ways (daily opioid use, MEDD, race, age, and percentages of diabetes, hypertension, and cardiovascular disease), it varied in both BMI (control group had a higher average BMI), and gender (control group had a greater number of male participants). It has been previously demonstrated that a higher BMI favors adherence to CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Despite the potential morbidity of the combination of OSA, central sleep apnea and Opioid use, studies have shown that those that have this combination only remain on definitive treatment for their OSA (CPAP) 37% of the time. [ 14 ] It is, therefore, of the utmost importance that patients who chronically use opioids are evaluated for OSA, and those diagnosed, adhere to CPAP.…”
Section: Introductionmentioning
confidence: 99%